Organizational and economic aspects of developing enterprises of passenger transpor - E. B. Lerman (Вестник СибАДИ, 2017)
The author has studied the condition and trends of developing enterprises of city passenger transport. The author has determined the peculiarities of functioning passenger services’ market of the region. There are presented priority directions of developing city transport as a socially significant economic system. The author has considered economic aspects of expediency of introducing automated system controlling passage when rendering passenger transport services.